ПРОБЛЕМИ ФІНАНСОВОГО ЗАБЕЗПЕЧЕННЯ ОХОРОНИ НАВКОЛИШНЬОГО ПРИРОДНОГО СЕРЕДОВИЩА В УКРАЇНІ - Карпишин, Наталія Іванівна (Науковий журнал «Світ фінансів», 2018)
Карпишин Н. І. Проблеми фінансового забезпечення охорони навколишнього природного середовища в Україні. Досліджено систему фінансового забезпечення охорони навколишнього природного середовища на сучасному етапі розвитку економіки України. Проведено моніторинг обсягів, складу і структури витрат на охорону довкілля за джерелами фінансування. Проаналізовано динаміку і склад власних витрат підприємств, організацій та установ за видами природоохоронних заходів та в розрізі регіонів. Розкрито систему екологічних платежів, динаміку надходжень і механізм розподілу екологічного податку між бюджетами. Проаналізовано динаміку і склад видатків державного і місцевих бюджетів на охорону навколишнього природного середовища. Вказано на основні недоліки системи фінансування довкілля та запропоновано напрямки їх усунення. Карпышин Н. И. Проблемы финансового обеспечения охраны окружающей природной среды в Украине. Исследована система финансового обеспечения охраны окружающей природной среды на современном этапе развития экономики Украины. Проведен мониторинг размера, состава и структуры затрат на охрану окружающей среды по источникам финансирования. Проанализирована динамика и состав собственных расходов предприятий, организаций и учреждений по видам природоохранных мероприятий и в разрезе регионов. Исследована система экологических платежей и динамика поступлений экологического налога и его распределение между бюджетами. Проанализирована динамика и состав расходов государственного и местных бюджетов на охрану окружающей среды. Указаны основные недостатки системы финансирования окружающей среды и предложены направления их устранения. Karpyshyn N. Problems financing of environmental protection in Ukraine. Introduction. The study of the current state of financing of environmental protection and the identification of the most significant problems and the ways of their solution is extremely a topical issue of modern financial science. Purpose is monitoring of the current state of financial provision of environmental protection in order to identify the most significant problems and propose ways of their solution, taking into account the domestic practice and the experience of European countries. Results. In 2016 the costs of environmental protection in Ukraine amounted to 32,5 billion UAH (excluding VAT) or 1,25 billion dollars. The largest share in the structure of these expenditures was made up by own funds of enterprises and organizations (68%), funds of state and local budgets were 6% and other sources of financing were 26,1%. Almost 70% of enterprise funds were used on waste water treatment and on waste management (including the processing of low-level radioactive waste, garbage composting, recycling). An extremely small amount of money was used to clean the air and climate change. The main tax, which has a special purpose and is the main budgetary source of financing of the environmental protection, is an environmental tax. Income instability of environmental tax revenues in the Consolidated Budget of Ukraine has been observed. Also chronic underperformance of the environmental tax revenues plan was in 2016 (33%), and in 2017 (24,8%). Expenditures of the consolidated budget on environmental protection in 2017 amounted to 7,3 billion UAH. The largest share of budget funds was spent on the needs of the exclusion zone in Chornobyl and on the operation of the state water management complex and water resources management. Only UAH 246,7 million was spent directly on environmental protection measures, which is an extremely insignificant amount, which is not enough to solve the existing environmental problems in the country. Conclusion. The main directions of improvement of financial provision of environmental protection in Ukraine: – to improve the efficiency of the current environmental tax; – to introduce new environmental taxes and taxes; – to ensure the targeted use of all ecological payments that come to the budgets; – to increase the efficiency of the use of environmental funds; – to change the method of calculation of fines for violation of environmental legislation; – to develop a system of preferential taxation for economic entities that use non-waste, resource-saving technologies.